Issuing International Bonds : A Guidance Note - van der Wansem, Patrick B. G.; Jessen, Lars; Rivetti, Diego (World Bank, Washington, DC, 2019)
Financial conditions in recent years have provided developing countries with unprecedentedopportunities to tap international bond markets, increasing access to commercial debtfinancing. On that background, developing countries are broadening the range of debtinstruments employed in implementing debt management strategies, and this has changed therisk profile of their public debt portfolios. The target audience of this Discussion Paper is thesovereign debt manager, with a special focus on first time/infrequent issuer in Low IncomeDeveloping Countries. The Guidance Note does not discuss whether countries should issueinternational bonds or not, but, rather, focus on the process of issuing such instruments, giventhe lack of objective and independent guidance available for issuers. The note outlines a stepby-step process and provides practical advice.